CHEMICAL EXPERIMENT - A METHOD OF VISUALIZATION AND ASSIMILATION OF THE LAWS OF CHEMISTRY - Дюжикова, Тетяна; Четвертак, Тетяна; Кулик, Ірина (SWorldJournal, 2026)
The concept of the New Ukrainian School requires teachers not only deep knowledge of their subject, but also a high level of methodological and practical training. One of the key components of the competency-based approach to studying natural sciences, in